Urban Street Food Buying Decision Toward Eco-Friendly Packaging: The Mediating Effects of Perceived Healthiness and Perceived Naturalness - Irlandra, Frendy; Christian, Michael (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
This study aims to examine the influence of Green Packaging (GP), Environmental Awareness (EA), and Willingness to Pay (WTP) on Purchase Decision (PD), with Perceived Naturalness (PN) and Perceived Healthiness (PH) serving as mediating variables among street food consumers in urban settings. The research methodology employs a quantitative approach via a survey technique. The sample comprised 161 street food patrons chosen through a purposive sampling method. The investigation was conducted utilizing the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique. The findings indicated that GP exerted no significant influence on the purchase choice, whereas EA and WTP demonstrated a positive and significant impact on BD when assessed directly. The association between green packaging mediated by perceived naturalness is favorable and substantial, however it is not significant when mediated by perceived healthiness. Environmental awareness shows a substantial and favorable correlation with BD, either directly or through mediation by PN and PH. The willingness to pay exerts a positive and substantial influence on BD; however, when mediated by PN, this effect is not significant, but mediation by PH results in a positive and significant effect.